Early palliative intervention: effects on patient care satisfaction in advanced cancer. Issue 2 (8th January 2021) - Mah, Kenneth; Swami, Nadia; O'Connor, Brenda; Hannon, Breffni; Rodin, Gary; Zimmermann, Camilla
Abstract : Objective: In a cluster-randomised controlled trial of early palliative care (EPC) in advanced cancer, EPC was robustly associated with increased patient satisfaction with care. The present study evaluated mediational mechanisms underlying this EPC effect, including improved physical and psychological symptoms and quality of life, as well as relationships with healthcare providers and preparation for end of life. Method: Participants with advanced cancer (n=461) completed measures at baseline and then monthly to 4 months. Mediational analyses, using a robust bootstrapping approach, focused on 3-month and 4-month follow-up data. Results: At 3 months, EPC decreased psychological symptoms, which resulted in greater satisfaction either directly (βindirect effect =0.05) or through greater quality of life (βindirect effect =0.02). At 4 months, EPC increased satisfaction through improved quality of life (βindirect effect =0.08). Physical symptom management showed no significant mediational effects at either time point. Better relationships with healthcare providers consistently mediated the EPC effect on patient satisfaction at 3 and 4 months, directly (βindirect effect =0.13–0.16) and through reduced psychological symptoms and/or improved quality of life (βindirect effect =0.00–0.02). At 4 months, improved preparation for end-of-life mediated EPC effects on satisfaction by enhancing quality of life (βindirect effect =0.01) or by reducing psychological symptoms and thereby increasing quality of life (βindirect effect =0.02). Conclusion: EPC increases satisfaction with care in advanced cancer by attending effectively to patients' emotional distress and quality of life, enhancing collaborative relationships with healthcare providers, and addressing concerns about preparation for end-of-life. Trial registration number: NCT01248624